Interfacial layers at a nanometre scale on iron corroded in carbonated anoxic environments. Issue 33 (6th April 2017) - Leon, Yoanna; Dillmann, Philippe; Neff, Delphine; Schlegel, Michel L.; Foy, Eddy; Dynes, James J.
Abstract : Two tests of iron corrosion in compacted clay and clay slurry were performed for several years. Abstract : Two tests of iron corrosion in compacted clay and clay slurry were performed for several years. The corrosion systems, and especially the interfacial layer between the metal and the corrosion products, were investigated post mortem by SEM-FEG, μRaman, MET and STXM. An Fe(iii ) oxide layer systematically developed at a nanometer scale between the metal and an outer layer of carbonates. Its presence could explain the slowing down of the corrosion rate usually observed for these systems. Depending of the compactness of the environment the nature of the interfacial layer is not the same.